Fashion students choose how to learn by constructing videos of pattern making - Cavanagh, Michaella; Peté, Marí (British journal of educational technology, 2017)
This paper analyses new learning experiences of first year pattern technology students at a university of technology, in the context of selected characteristics of authentic learning theories. The paper contributes to existing knowledge by proposing a method that could be followed for design‐based subjects in a vocational education setting. Students were competent when replicating demonstrated pattern making procedures, but struggled to transfer knowledge to different situations. Therefore, a project asked students to create their own pattern‐making video tutorials in an effort to deepen authentic learning. Examining the learning activity and its results through action research reflection, the lecturer recognised authentic learning characteristics. For example, students grasped the work, displaying a range of original responses that presented more than one correct answer. By creating their own practice‐based content, students were able to learn more in the same period, compared to other cohorts in past years. Students were better equipped to utilise this knowledge in later projects and tests, demonstrating deeper understanding and knowledge transfer to other environments. Ultimately active knowledge production deepened learners' motivation, engagement in the learning process, and increased performance.